• Упростите выражение:
    1)(72a2b4-11a2b2):(ab)+(8ab)*(-9a2b2)=
    2)(63a3b2+45a2b):(9a2b)-(56a2b3):(8ab2)=
    3)(4,4x3y4+5,5x4y3):(1,1xy)-(8xy2-12x2y)*(0,5xy)=

Ответы 1

  • a^2b2(72b2-11):ав - 72а3b3=72ab3-72a3b3=72ab3(1-a2)9a2b(7ab+5b):9а2b - 7ab=7ab+5b-7ab=5b1.1x3y3(4y+5x):1.1xy - x2y2(4y-6x)=x2y2(4y+5x) - x2y2(4y-6x)=x2y2(4y+5x-4y+6x)=11x3y2
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years